Analisis Risiko pada Unit Critical Asset Menggunakan House of Risk pada Perusahaan X - Samodro, Guntur; Cahyo, Winda Nur (Universitas Muhammadiyah Sorong, 2025)
Clean water is one of the basic needs for human life. The toughest challenge related to clean water problems is in the procurement and distribution of clean water. Instability in distribution and supply chain issues has now become one of the company's focuses of attention. The success of the company depends on the structure and alignment of the supply chain design, this can be done if the company is able to minimize the negative effects of the risk of critical assets. Understanding the concept of asset management is important. This study aims to design and implement an asset management policy model in the case of critical assets in Company X, especially in the K water house. After an analysis was carried out using the House of Risk phase 1 and the Pareto diagram, the results were 14 risk agents (Risk Agent) which are a description of 6 risk events (risk events) that are included in the vulnerable and high-risk categories. After an analysis was carried out using the House of Risk phase 2 and an assessment of the Effectiveness to Difficulty Ratio (ETD) value, 22 priority risk management strategies (PA) were obtained. One of these risk management strategies is the policy of installing a soft starter for the pump panel.